The Relationship Between the Sheikh Bizeni Tribe and the Residents of Koya City and its Surroundings (1900-1905): A Historical-Documentary Study - Abdulsamad, Zana T. (KOYA UNIVERSITY JOURNAL OF HUMANITIES AND SOCIAL SCIENCES, 2025)
When governmental institutions in any region weaken and lose their influence and authority, other forces emerge in their place, leading to conflicts and disagreements among these emerging powers. Koya was one of the cities where Ottoman authority had significantly weakened by the early nineteenth century, leading to raids by surrounding tribes against its residents. This research focuses on the Sheikh Bizeni tribe, one of the most prominent. This study attempts to answer three research questions: What were the causes of confrontations between the Sheikh Bizeni tribe and the residents of Koya? What role did Ottoman state institutions play in this conflict? How much damage did these raids inflict on the local population? We attempt to address all these questions by presenting official Ottoman state documents and contemporary sources of the events, along with analysis of the information. As indicated above, we aim to shed light on a historical event that significantly impacted various aspects of the city's development. Furthermore, the existence of such a conflict during that period reveals the weakness of Ottoman authorities, who often could not easily resolve these issues and had to resort to other forces to confront this antagonism. After looking at the documents, as academic researchers we tried to give readers an unbiased account of this event, focusing on the part that Hama Agha Ghafuri played along with the people who lived in the city in response to the Sheikh Bizeni tribe's conflict and hostility toward Koya city.